Child with Susceptibility to Infection-Induced Acute Encephalopathy 3 - Khalil, Ayman; Malalla, Husain Ali Ahmed; Naser, Husain; Almuslamani, Ahood (Journal of Pediatric Neurology, 2019)
A 10-month-old Bahraini boy born full-term to first-degree cousins, initially had normal developmental milestones, but presented with recurrent encephalopathy and seizures associated with upper respiratory tract infection. With each attack, the patient developmentally regressed further. Brain magnetic resonance imaging showed multiple old and new infarcts. Cerebrospinal fluid biochemistry, microbiology, and amino acids were unremarkable. Tandems mass spectrometry of urine organic acids was unremarkable as well. Electroencephalogram showed asymmetry with cortical irritability. Whole exome sequencing revealed a homozygous mutation of RAN-binding protein 2 gene, suggesting a diagnosis of susceptibility to infection-induced acute encephalopathy 3, which is an autosomal dominant condition. This is the first case to be reported in Bahrain.
Keywords: RANBP2; susceptibility to infection-induced acute encephalopathy 3; acute necrotizing encephalopathy; ANE1; RAN-binding protein 2